2007
DOI: 10.1016/j.brainres.2007.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Apnea promotes glutamate-induced excitotoxicity in hippocampal neurons

Abstract: Patients with obstructive sleep apnea (OSA) exhibit hippocampal damage and cognitive deficits. To determine the effect of apnea on the synaptic transmission in the hippocampus, we performed electrophysiological studies in an in vivo guinea pig model of OSA. Specifically, we determined the cornu ammonis region 1 (CA1) field excitatory postsynaptic potential (fEPSP) response to cornu ammonis region 3 (CA3) stimulation and examined the presynaptic mechanisms underlying the changes in the fEPSP. Single episodes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…Given the lower NAA, the higher glutamate levels could reflect greater astrocyte activation (Kimelberg et al, 1990; Szatkowski et al, 1990), perhaps as a compensatory mechanism attempting to correct for lower neural activity. In addition to altering function, high levels of extracellular glutamate lead to excitotoxicity and in apoptosis of neurons (Fung et al, 2007). Hence, high glutamate is consistent with low NAA if the latter is considered a marker of neuronal cells (as opposed to neuronal function).…”
Section: Discussionmentioning
confidence: 99%
“…Given the lower NAA, the higher glutamate levels could reflect greater astrocyte activation (Kimelberg et al, 1990; Szatkowski et al, 1990), perhaps as a compensatory mechanism attempting to correct for lower neural activity. In addition to altering function, high levels of extracellular glutamate lead to excitotoxicity and in apoptosis of neurons (Fung et al, 2007). Hence, high glutamate is consistent with low NAA if the latter is considered a marker of neuronal cells (as opposed to neuronal function).…”
Section: Discussionmentioning
confidence: 99%
“…For example, FUNG et al [33] suggested that intermittent hypoxia produces abnormally high level of glutamate and causes excitotoxicity in hippocampal neurons. LI et al [34] concluded from their study that intermittent hypoxia in the rat is associated with an increased expression of iNOS which may play a critical role in IH-mediated neurobehavioural deficits.…”
Section: Reviewmentioning
confidence: 99%
“…Intermittent hypoxia (IH), one of the pathophysiologic changes resulting from obstructions of the upper airway during sleep, may play a key role in the structural neuron damage in the CNS, especially excitotoxicity in hippocampal neurons [8,9,36]. Moreover, IH would lead to the up-regulation of ROS, NO, and downstream pro-inflammatory responses [2,30].…”
Section: Introductionmentioning
confidence: 99%